Approaches to flexicurity - EU models - Philips, Kaia; Eamets, Raul (Luxembourg, 2007)
"This report compares the various flexicurity options across 25 Member States – including models of best practice – while looking at how flexicurity is measured in these countries and identifying the challenges related to its implementation in the different countries. It explores the three pillars of the flexicurity model: social protection, labour market adaptability/flexibility and social inclusion. It also highlights the crucial role played by the social partners in the process."